Impact of Surgical Timing on Management of Acute Appendicitis: A Comparative Retrospective Study - Abdalla M. M. Etbiga; Hend Fathi; Farag Sakot (Libyan Journal of Medical and Applied Sciences, 2025)
Background: The optimal timing for surgical intervention in acute appendicitis remains a subject of ongoing debate. This study aimed to compare the clinical outcomes of early versus delayed appendectomy, and to assess the feasibility and safety of delayed surgical management. Methods: A retrospective review was conducted on medical records of patients who underwent appendectomy for acute appendicitis between April 1, 2023 and April 30, 2024. Patients were divided into two groups based on the period between when the patient was admitted to the hospital and when the surgery started: Group A (≤ 8 hours) and Group B (> 8 hours). Primary outcomes included white blood cell (WBC) count on the first postoperative day, time to initiation of soft diet, complication rate, surgical site infection (SSI) rate, length of hospital stay, and readmission within two weeks. Results: Out of 354 patients, 48 were excluded according to predefined criteria, leaving 306 patients for analysis. Group A included 164 patients (53.6%), and Group B included 142 patients (46.4%). Baseline demographic and clinical characteristics showed no meaningful differences between Group A and Group B. Group B had lower mean WBC counts on postoperative day one compared to Group A (p 0.0052). There were no notable variations between the groups in terms of time to resume a soft diet, duration of hospitalization, incidence of complications, or readmission within two weeks. SSI occurred in 3 patients (1.8%) in Group A and 5 patients (3.5%) in Group B (p = 0.2260), showing no statistically significant difference. Conclusions: Delayed appendectomy (> 8 hours) is a safe and feasible option for adult patients with acute appendicitis. Although delayed surgery did not demonstrate superior clinical outcomes compared to early appendectomy, the timing of intervention can be adapted based on hospital workflow and resource availability.